Cycloid Gear Profile Modification based on Elliptical Method - Chen Zhilong; Wang Jun; Qin Zhengzheng; Zhao Daxing; Wang Quan (Jixie chuandong)
In order to get a more ideal cycloidal profile,a new cycloid profile modification method is proposed. Under the circumstance of keeping the short coefficient and the eccentricity constant,the contour line of the modified tooth profile is obtained by the elliptical crocheting of the standard theoretical contour line,and the expression of the equation is deduced. Compared with the commonly used method of tooth profile modification,the modified tooth profile curve is much closer to the complete conjugate tooth profile on the main meshing areas,and the meshing clearance between the cycloid wheel and the pin wheel can be made adjustment by controlling the shape parameters of the ellipse,which is simple and flexible. The normal tooth profile clearance,initial meshing clearance,contact stress and backlash are analyzed to verify the rationality of the modified method.